Mathematical Modeling of CO2/CH4 Separation by Hollow Fiber Membrane Module Using Finite Difference Method - Shamsabadi, Ahmad Arabi; Kargari, Ali; Farshadpour, Foroogh; Laki, Saeed (Journal of Membrane and Separation Technology, 2012)
Removal of CO2 in landfill gas recovery processes and fractured wells as well as its application in enhanced oil recovery and its environmental aspects are of interest. Also separation of CO2 from CH4 in Ethylene Oxide plant is an environmental policy of Marun Petrochemical Company. In the present work, a shell-fed hollow fiber module was modeled mathematically for CO2 separation from CH4. Finite difference method was used for solving the equations. Comparison between co-current and counter-current flow patterns showed that for all conditions, counter current pattern had better efficiency for CO2/CH4 separation. Influence of operating parameters such as feed pressure, permeate pressure, feed flow rate, fiber length and CO2 concentration of feed on separation efficiency of CO2/CH4 mixture was investigated. Also the effect of feed and permeate pressures on required membrane area showed that the membrane area increases by increasing permeate pressure and decreases by increasing feed pressure. The modeling offers valuable data about feasibility study and economical evaluation of a gas separation unit operation as a helpful unit in the industry.